Spectral‐domain optical coherence tomography of retinal vessels in Waldenström's macroglobulinemia. Issue 2 (18th August 2019) - Willerslev, Anne; Larsen, Michael; Rothenbuehler, Simon P.; Sørensen, Torben L.; Hammer, Troels; Paques, Michel; Munch, Inger Christine
Abstract: Purpose: To image retinal blood vessels in patients with Waldenström's macroglobulinemia using optical coherence tomography (OCT). Methods: Retrospective case series examining fundus photographs and OCT scans of 16 eyes in eight patients with Waldenström's macroglobulinemia. Analyses included intravascular OCT reflectivity profiles and vessel diameters, and their relation to total immunoglobulin M (IgM) levels. Results: In six out of eight patients, cross‐sectional OCT scans of larger retinal vessels (diameter > 100 μm) showed normal intravascular reflectivity and retrovascular shadowing. In two patients with the highest total IgM > 60 g/l, altered intravascular reflectivity, distinct anterior and posterior vessel wall reflexes, and retrovascular hyposhadowing were seen. Normalization of the OCT reflectivity in these patients occurred after reduction of total IgM to < 17 g/l and was accompanied by decreasing venous tortuosity and disappearance of retinal haemorrhages and cotton wool spots. Conclusion: This study found that Waldenström's macroglobulinemia and total IgM > 60 g/l were associated with abnormal intravascular reflectivity and retrovascular shadowing on OCT. Awareness of these signs of hyperviscosity could potentially enable earlier detection of critical conditions in patients with Waldenström's macroglobulinemia and improve the assessment of severity and treatment effect.